Народництво, модернізм і постмодернізму лінгвістиці тексту - Монахова, Т.В. (Мовознавство, 2013)
Стаття присвячена лінгвістичному осмисленню понять «народництво», «модернізм» і «постмодернізм», розглянутих як стратегії текстотворення в сучасній українській мові. Виявлено основні мовні ознаки кожної зі стратегій текстотворення. Проаналізовано способи взаємодії народницької, модерністської та постмодерністської стратегій текстотворення в діахронічному й синхронічному аспектах. This article deals with the linguistic concepts of the populism, modernism and postmodernism which are the strategies of the modem Ukrainian language. The basic linguistic features of the each strategy are given. The ways of interaction the populism, modernism and postmodernism strategies of text in diachronic and synchronic aspects are examined. Text-building strategy is a way of text messaging which depends on speaker's attitudes and his intentions while speaking, has a clear plan for verbal expression, represented by certain techniques and tactics of text creating due to the internal laws of the language. The populism in linguistics of the text is the strategy of text-building, characterized by the focus on the Ukraine, moralistic pathos, didacticism, postcolonial complex, linguistic purism, classical rhetoric and sacralization of certain taboo topics and layers of vocabulary, lexical closeness to the excessive borrowing, traditional Ukrainian ethnic concepts, etc. Modernism is the text-building strategy, characterized by the openness to cultural and linguistic borrowing, destruction stamps of previous eras, activation of the discourse of women’s and gender studies in general, etc. The origins of modernism researchers are in the speakers’ effort to create a new text type to influence recipients. Among the many tactics of the postmodern text-building strategy we can name intertextuality, language game as a law of the existence of modem language, the language of the Internet as a special social dialect today, linguistic kitsch, etc. Thus, the attempts of the linguistic reterminologization of the three important and urgent social terms have been done in this paper.